The Impact of Information Systems on Port Performance: The Case of Morocco’s Agadir Port - Jouad, Soukaina; Hamri, Mohammed Hicham (European Scientific Journal, ESJ, 2020)
The objective of this research paper is therefore to examine the role of information systems in improving the port performance of Agadir. This study highlights how the port supply chain deploying information systems can improve performance by stimulating collaboration between multiple port operators. This research adopted a descriptive survey design. To achieve the objectives of the study, primary data was collected using a semi-structured questionnaire. The study concludes that the use of information systems reduce vessels stays and improves the productivity of ships at berths. Based on these results, the study concludes that the capacity to use and manage information systems in a much more effective and efficient way can improve the performance of the kingdom’s port.